Akulturasi Religi dengan Kesakralan Tradisional Suku Bangsa Lanny - Kogoya, Abisay; Hijjang, Pawennari; Poli, Agustina Ivonne; Numberi, Gerdha K.I. (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This study aims to explore in depth the process of Acculturation of Religion and Sacredness in the Lanny Tribe in Lanny Jaya Regency. Then, analyzing the form of religious acculturation and sacredness in the Lanny tribe in Lanny Jaya Regency. As well as uncovering the Implications of Acculturation of Religion and Sacredness to the Lanny Tribe in Lanny Jaya Regency. This study uses qualitative research methods with a phenomenological approach. Determination of key informants is done in a snowball manner by determining key informants who guide the researcher in determining the next informant. Data collection techniques used were in-depth interviews, observation, and focus group discussions. Data analysis includes the stages of preparing data, reading all data, coding data, analyzing data, and interpreting data by putting it in the form of interpretive narratives. The results showed that the acculturation process was carried out with the process of introducing Christian religious teachings which was carried out peacefully and persuasively, even though there had been tension, but it did not last long. forms of acculturation that occur include substitution, syncretism, addition, deculturation, and rejection. These forms of acculturation experience their respective adjustments, both from traditional sacred practices and the Christian religion. The implications of acculturation have a very significant impact on changes in the lifestyle of the Lanny people, such as orientation in life.